The optimism of the wise in Israel and in Africa : helpful in the time of HIV / AIDS? - Masenya, Madipoane (Old Testament essays, 2005)
South African church leaders, theologians and biblical scholars who take comfort in succumbing to the status quo should be compelled by the high incidences of AIDS-related deaths on the African continent, to rethink their stance. In the light of how the Christian Bible has been used and continues to be used to support patriarchy in all its manifestations among Black women, and given the harsh reality that patriarchy, particularly in Sub-Saharan Africa, breeds fertile soil for the HIV Virus, there is a need to make a shift from traditional and insufficient biblical interpretations, particularly if the latter fail to provide solutions to the complex nature of the HIV / AIDS pandemic in our midst. The optimistic wisdom philosophy of the wise in Israel, a philosophy rooted in the status quo of the time, sets great store by the notion of rewards and punishments. It was believed that through experiential wisdom, life could be mastered to the extent that easy solutions could be provided, as in the following belief: Live righteously and be blessed and lead an unrighteous life and bear its negative consequences. Such a simplistic wisdom philosophy, as will be revealed from an analysis of a few African-South African proverbs in the present text, also underlies the African worldviews. The main question addressed in this paper is: Given the complex nature of factors that contribute to the fast spread of the HIV virus in poverty-stricken contexts as well as the stigma that continues to accompany AIDS sufferers in our midst, how helpful is such a philosophy in our fight against HIV / AIDS?